China's integration in East Asia the role of intra-industry trade - Tan, Elizabeth S. (The Philippine Review of Economics, 2010)
China's intra-industry trade (IIT) with East Asia was minimal during the early years of opening up from 1978 to 1993 but increased relative to inter-industry trade in the post-1993 years. Bilateral intra-industry (BIIT) trade with Japan and Korea was sustained in capital-intensive heavy industries such as metals and yarns; its BIIT with East Asian countries also increased tremendously starting 1993 in industries characterized by production networks.